The Descriptions of Monitoring in Reading on Students' English Reading Material at SMA Swasta Santu Xaverius Gunungsitoli - Telaumbanua, Enjerlin; Harefa, Afore Tahir; Zega, Riswan; Telaumbanua, Kristof Martin Efori (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Reading ability in English has been an essential skill for high school students, yet many students have experienced difficulties in comprehending English texts effectively. One factor suspected to be the cause of this problem was the students’ lack of ability to monitor their reading process. This research aimed to describe the monitoring in reading on students' English reading materials and to identify the dominant components in students' reading monitoring. The research was conducted at SMA Swasta Santu Xaverius Gunungsitoli used a qualitative descriptive approach. Data were collected through observations and interviews with 36 tenth-grade students. The results showed that students applied three main components in reading monitoring: Comprehension Monitoring, Metacognitive Monitoring, and Comprehension Evaluation. Monitoring Comprehension emerged as the most dominant strategy that students reported using. The most frequently used strategies were rereading difficult passages, underlining important passages, and taking notes. Metacognitive monitoring was reported by students, with a focus on identifying difficulties in texts and reflecting on reading content. Comprehension Evaluation was used by students, particularly in answering text-related questions and identifying main ideas. In conclusion, most students have demonstrated good awareness of their reading process and have actively used various strategies to improve their comprehension of English texts. However, there is still room for improvement, especially in the aspects of metacognitive monitoring and the use of more complex strategies.